Plano de Projeto: Suíte de Comunicação - Cysne, Rommel (Universidade do Vale do Rio dos Sinos, 2018)
This paper aims to present a project plan for the implementation of a corporate communications suite. The document contemplates the project management plan, containing the integration, scope, time, cost, quality, human resources, communications and risk management plans necessary for good project management practice. All plans where developed following the practices for project management and disseminated by the Project Management Institute (PMI) through the PMBOK – Project Management Body of Knowledge Guide.
Keywords: Plano de gerenciamento de projeto; Project management plan